‘Let us now invoke the three celestial lights of Fire, Sun and Moon into ourselves’ - Hirmer, Monika (Tantra, Magic, and Vernacular Religions in Monsoon Asia, 2022)
This chapter tries to depart from the positivistic existential outlook cast by Western scholarship on the ‘magical’ rituals carried out by South Indian Śrīvidyā practitioners to cultivate oneness with goddess Tripurasundarī. Hirmer explores the ontological coordinates that accommodate this oneness cogently and unambiguously and proposes a radical re-evaluation of the concept of ‘beingness’ as conceived by a modern scientific framework, revealing an emic understanding where bodies expanding into subtle realms and actions partaking in cosmic designs respond to ontological coordinates informed by transcendence. The ontological dislocation she advocates, where identities and practices deviating from a positivistic framework need no longer be confined to the domain of ‘magic’ but can be appreciated in their ontological primacy and epistemic legitimacy, invites novel, decolonial, modes of approaching the Śrīvidyā tradition and Tantric traditions generally.<br